The effect of blood pressure variability on the prognosis of hypertensive patients - Ziad A Taher; Waleed W Khayyat; Marwan M Balubaid; Mohamed Y Tashkandi; Haifaa Akif Khayyat; Abdulhalim Jamal Kinsara (Anatolian Journal of Cardiology)
Objective: Our study aims to compare the effects of blood pressure variability (BPV) during ambulatory blood pressure measurement (ABPM) and visit-to-visit measurements to predict future cardiovascular complications among hypertensive patients. Methods: This is a retrospective case-control study of patients with hypertension over 10 years. All adult patients with at least one recorded ABPM, and at least three recorded visit measurements were included. Patients with incomplete ABPM readings, a history of a tested outcome, or the occurrence of any of the tested outcomes within the measurement period were excluded. The outcome was the development of any of the following: acute coronary syndrome (ACS), chronic ischemic heart disease (IHD), heart failure (HF), or stroke. Results: Of the 305 cases reviewed, 152 were included. The mean follow-up was 6.6+-2.3 years. The mean age was 53.5+-14.3 years. Eighty-two (53.9%) patients were male, while 70 (46.1%) were female. Risk factors included diabetes mellitus (53.9%), dyslipidemia (39.5%), obesity (16.4%), and smoking (8.6%). Comorbidities included stroke (2%), ACS (8.6%), IHD (20.4%), HF (2.6%), and renal failure (1.3%). One or more complications were seen in 22.4 % of the included patients. The variation of the daytime systolic ABP had been found to predict the future risk of developing IHD (OR=1.94; 95% CI=1.09–3.45; p=0.025). Moreover, IHD was associated with night-time systolic standard deviation (SD) in ABPM (OR=1.23; 95% CI=1.00–1.51; p=0.048). On the other side, ACS was found to be associated with systolic SD in visit-to-visit measurement (OR=1.10; 95% CI=1.01–1.21; p=0.04). Conclusion: Hypertensive patients with high variability of daytime and night-time SD in ABPM are more likely to have IHD. Whereas, having high variability in systolic SD in visit-to-visit measurements is associated with developing ACS.